Organic cation directed one-dimensional cuprous halide compounds: syntheses, crystal structures and photoluminescence properties. Issue 27 (11th June 2019) - Yue, Cheng-Yang; Lin, Na; Gao, Lu; Jin, Ying-Xue; Liu, Zhao-Yang; Cao, Yao-Yao; Han, Sha-Sha; Lian, Xi-Kai; Hu, Bing; Lei, Xiao-Wu
Abstract : One-dimensional organic–inorganic hybrid cuprous halides exhibit strong tunable photoluminescence from cyan to red emissions with large Stokes shifts. Abstract : In recent years, organic–inorganic hybrid metal halides have emerged as a highly promising class of semiconducting light emitting diodes (LEDs) due to their fascinating photoluminescence properties. Here, by specifically selecting different organic cations as templates, a series of new hybrid cuprous halides have been solvothermally prepared, namely [Me-Py]CuI2 (1 ), [(Me)2 -DABCO]Cu2 I4 (2 ), [Me-MePy]Cu2 I3 (3 ), and [H2 DABCO]Cu3 X5 (X = I (4 ) and Br (5 )). These hybrid cuprous halides feature one-dimensional (1D) [CuI2 ] −, [Cu2 I3 ] − and [Cu3 X5 ] 2− (X = Br, I) chains surrounded and charge-balanced by organic cations. Under UV photoexcitation, these hybrid cuprous halides exhibit strong tunable photoluminescence from cyan (480 nm) to red (675 nm) emissions with large Stokes shifts (345 nm). The intrinsic nature of PL emissions is also investigated based on temperature-dependent PL emission, lifetime, photoluminescence quantum efficiencies, etc .